Progress on the Mechanism of Visceral Hypersensitivity in Nonerosive Reflux Disease - Cao Xu; Xiaoping Niu (Gastroenterology Research and Practice)
Nonerosive reflux disease (NERD) is the most common type of gastroesophageal reflux disease (GERD). Its clinical symptoms can recur, and clinical treatment is often ineffective, causing patients severe economic and psychological burden. In recent years, studies that have explored in-depth the pathogenesis of NERD have found that visceral hypersensitivity (VH) plays an important role. VH refers to the phenomenon that viscera react strongly to nociceptive stimuli or produce a negative reaction to physiological stimuli due to the decrease of one’s visceral pain threshold. Studies have found that the VH mechanism in NERD primarily includes abnormal neurotransmitters, the activation of acid-sensitive receptors, and abnormal psychological factors—all of which we review in this article.